183k views
2 votes
Let m = 6x + 5.

Which equation is equivalent to (6x + 5)2 – 10 = -18x – 15 in terms of m?

User Tim Trout
by
4.5k points

2 Answers

5 votes

Answer:

m = 2

Explanation:

(6x + 5)2 – 10 = -18x – 15

12x + 10 - 10 = -18x - 15

12x + 18x = -15

30x = -15

x = -15/30

x = -1/2

m = 6x + 5

m = 6(-1/2) + 5

m = -3 + 5

m = 2

User Thule
by
5.2k points
5 votes

Answer:

m² + 3m - 10 = 0

Explanation:

Given

(6x + 5)² - 10 = - 18x - 15 ← factor out - 3 from each term

(6x + 5)² - 10 = - 3(6x + 5)

Now let m = 6x + 5 in the equation, that is

m² - 10 = - 3m ( add 3m to both sides )

m² + 3m - 10 = 0

User Tcbrazil
by
5.5k points